GABARAP is a determinant of apoptosis in growth‐arrested chicken embryo fibroblasts. Issue 7 (July 2015) - Maynard, Scott; Ghosh, Romita; Wu, Ying; Yan, Shi; Miyake, Tetsuaki; Gagliardi, Mark; Rethoret, Karen; Bédard, P‐A.
Abstract : Nutrient depletion triggers a series of adaptive processes as part of the unfolded protein response or UPR. These processes reduce stress to the endoplasmic reticulum by enhancing its protein folding capacity or ability to promote the degradation of dysfunctional proteins. Failure to restore ER homeostasis causes the activation of lethal pathways. The expression of a dominant negative mutant of C/EBPβ (Δ184‐C/EBPβ) alters this balance in chicken embryo fibroblasts (CEF). As a result, CEF display enhanced survival upon prolonged nutrient depletion. Starved Δ184‐C/EBPβ–expressing CEF display pronounced features of autophagy characterized by the appearance of large vesicles containing amorphous material, the formation of smaller double‐membrane vesicles (autophagosomes) and processing of LC3 and GABARAP. However, there were marked differences in the expression and processing of these proteins. In both normal and Δ184‐C/EBPβ expressing CEF, the lipidated form of LC3 (form II) accumulated during starvation but was detectable even when cells were actively dividing in complete medium. In contrast, GABARAP expression and lipidation were strongly stimulated in response to starvation. Inhibition of LC3 expression by RNA interference led to apoptosis in normal CEF even in the absence of starvation but stable and near complete repression of GABARAP was tolerated. Moreover, the inhibition of GABARAP enhanced CEF survival and abolished the expression of the pro‐apoptotic CHOP factor in conditions of starvation, suggesting a reduced level of ER stress. Therefore, GABARAP is a determinant of apoptosis in CEF subjected to prolonged nutrient depletion. J. Cell. Physiol. 230: 1475–1488, 2015. © 2014 Wiley Periodicals, Inc., A Wiley Company